The End of Lawyers? : Rethinking the Nature of Legal Services - Susskind, Richard (Oxford : Oxford University Press, 2010)
This widely acclaimed legal bestseller has ignited an intense debate within the legal profession. It examines the effect of advances in IT upon legal practice, analysing anticipated developments in the next decade. It urges lawyers to consider the sustainability of their traditional role
Includes bibliographical references (p. 285-291) and index
eng.
Keywords: Practice of law Automation; Justice, Administration of Automation; Technology and law